Pengaruh Recovey Aktif dan Pasif Dalam - Heru Syarli Lesmana; Padli Padli; Endang Pati Broto (Fakultas Ilmu Olahraga, Universitas Negeri Surabaya, 2018)
A B S T R A C TPhysical exercise causes athletes to be at risk of injury. One of the most common muscle injuries is Delayed Onset Muscle Soreness (DOMS). DOMS is a pain felt by a person within 24-72 hours after sports activities. Active recovery is a physical activity that do in low intensity. Passive recovery means stop activity and not doing anything or total rest. This research is expected to find the type effective and efficient recovery in reducing DOMS symptoms. The type of this research is quasi experiment with the three group post-control group design. The sample is a student of Faculty of Sport Science State University of Padang which is divided into 3 groups. Each group consists of 15 students. Each Sample will perform an eccentric physical exercise by squatting 10 sets (1set: 20 steps) with a break for 30 seconds each set. After exercie group 1 didnt do recovery, group 2 did a passive recovery and group 3 did active recovery. After 48 hours, DOMS measurements were made using Visual Analog Scale (VAS). Research data is tabulated and analyzed with descriptive statistic test, distribution normality test, homogeneity test, different test. Result of data analysis concluded there is effect of active recovery to DOMS symptom with p 0,005. There is no effect of passive recovery of DOMS symptoms with p 0, 180. Conclusion active recovery research can reduce DOMS symptoms.